The Impact of the Transition to International Accounting and Auditing Standards on Audit fees from the Perspective of the External Auditors in Saudi Arabia: A Field Study - Al - Mahmadi, Hanan Abdullah Hamed (Journal of Economic, Administrative and Legal Sciences, 2018)
The aim of the research was to identify the impact of the transition to international accounting and auditing standards on the audit fees from the point of view of the external auditors in Saudi Arabia. The inductive and descriptive analytical method was used. The tool was in a questionnaire that was applied to a random sample of 68 reviewers. The results of the study showed that the impact of the shift to the international accounting and auditing standards on the audit fees from the point of view of the external auditors in Saudi Arabia and at the general level of the tool has obtained a general average (3.98 of 5) The three pillars of the research were the implementation of the factors related to the international accounting and auditing standards; the overall average (4.12 of 5); followed by the axis; the impact of the application of international standards for the first time, obtained a total average of (3.92) And audit risk for financial statements prepared in accordance with the criteria See International; an average total (3.90), all of which degree the impact of (large), These averages confirm the consensus of the sample to increase the cost of the audit, which is reflected in the increase in audit fees. In the light of the results, the researcher recommended that the employees in the field of accounting and auditing should be attached to specialized training courses in the field of international accounting standards. With emphasis on the importance of teaching international accounting and auditing standards and intensively in Saudi universities, with workshops to allow university students to learn about the reality and face the labor market. And to benefit from the experiences of countries that have applied international standards; to find out the problems that accompanied the implementation process, and the proposed solutions, especially countries that approach the environment of Saudi Arabia, and suggested titles for complementary studies to meet the ambiguities on the subject.